High-strength unbonded prestressed steel bar and production process thereof

Through the combination and modification of modified magnesium oxide whiskers and calcium carbonate, combined with lubricants, the tensile performance of the non-bonded prestressed steel rod sheath is improved, and the problem of poor sheath performance is solved, and the High strength and good toughness, suitable for prestressed components in concrete structures.

CN119308472APending Publication Date: 2025-01-14HEBEI JINKUN ENG MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411461726.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The sheath tensile performance of the non-bonded prestressed steel rods affects its application in structural stress and construction.

Method used

Use polyethylene, ethylene-vinyl acetate, magnesium oxide whiskers and calcium carbonate to form modified magnesium oxide whiskers and modified calcium carbonate through modifiers such as 2,5-dihydroxybenzoic acid or fatty acid. Improve the tensile properties of the sheath and coat the surface of the prestressed steel rod through the extrusion process through the combination of lubricant, antioxidant and light stabilizer.

Benefits of technology

It significantly improves the tensile strength and elongation of break of the sheath, extends the service life of the non-bonded prestressed steel rod, and provides high strength and good toughness in the concrete structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of building components, and provides a high-strength unbonded prestressed steel bar and a production process thereof. The high-strength unbonded prestressed steel bar comprises a prestressed steel bar body, lubricating oil and a sheath, the sheath is prepared from, by mass, 100 parts of polyethylene, 30 parts of ethylene-vinyl acetate, 10-20 parts of filler, 0.5-1 part of a lubricating agent, 0.5-2 parts of an antioxidant and 0.1-0.5 part of a light stabilizer, and the filler comprises magnesium oxide whiskers and calcium carbonate according to the mass ratio of 1: 9-9: 1. According to the technical scheme, the problem that the tensile property of the sheath of the unbonded prestressed steel bar is poor in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building components, and in particular to a high-strength unbonded prestressed steel rod and a production process thereof. Background Art

[0002] With the rapid development of prestressed technology, prestressed materials and process equipment are changing with each passing day. Prestressed steel bars are essentially steel bars, which are mainly used as prestressed components in concrete structures. They use prestressing force to make up for the defects of concrete itself, making it less likely to break when under pressure.

[0003] With the continuous advancement of technology, unbonded prestressed steel bars have been widely used in prestressed components due to their advantages in structural stress and ease of construction. Unbonded prestressed steel bars refer to steel bars that are first coated with a lubricating coating on the surface and then wrapped with a sheath made of polyethylene resin extruded on the outermost layer. The tensile properties of the sheath affect the use of unbonded prestressed steel bars. Therefore, how to improve the tensile properties of the sheath is a technical problem that needs to be solved urgently. Summary of the invention

[0004] The invention provides a high-strength unbonded prestressed steel rod and a production process thereof, which solves the problem of poor tensile performance of a sheath of the unbonded prestressed steel rod in the related art.

[0005] The technical solution of the present invention is as follows: A high-strength unbonded prestressed steel rod comprises a prestressed steel rod, lubricating oil and a sheath. The raw materials of the sheath comprise the following components in parts by mass: 100 parts of polyethylene, 30 parts of ethylene-vinyl acetate, 10-20 parts of filler, 0.5-1 part of lubricant, 0.5-2 parts of antioxidant, and 0.1-0.5 parts of light stabilizer. The filler comprises magnesium oxide whisker and calcium carbonate in a mass ratio of 1:9-9:1.

[0006] As a further technical solution, the lubricant may be any one or more lubricants in the art, preferably lubricant AC-540A.

[0007] As a further technical solution, the antioxidant may be any one or more antioxidants in the art, preferably one or more of antioxidant 168, antioxidant 1010, and antioxidant 626.

[0008] As a further technical solution, the light stabilizer can be any one or more light stabilizers in the art, preferably one or both of light stabilizer UV-144 and light stabilizer UV-531.

[0009] As a further technical solution, the magnesium oxide whisker is a modified magnesium oxide whisker, the calcium carbonate is a modified calcium carbonate, and the modifiers in the modified magnesium oxide whisker and the modified calcium carbonate are each independently 2,5-dihydroxybenzoic acid or fatty acid.

[0010] As a further technical solution, the raw materials of the modified magnesium oxide whisker include a modifier and magnesium oxide whisker in a mass ratio of 0.3 to 1.2:20.

[0011] As a further technical solution, the raw materials of the modified calcium carbonate include a modifier and calcium carbonate in a mass ratio of 0.5 to 1.5:20.

[0012] In the present invention, the magnesium oxide whisker and the calcium carbonate are respectively modified by 2,5-dihydroxybenzoic acid or fatty acid, so that the tensile properties of the sheath are further improved.

[0013] As a further technical solution, the modifier in the modified magnesium oxide whisker is fatty acid, and the modifier in the modified calcium carbonate is 2,5-dihydroxybenzoic acid.

[0014] In the present invention, the modifier in the modified magnesium oxide whisker is limited to fatty acid, and the modifier in the modified calcium carbonate is limited to 2,5-dihydroxybenzoic acid, which further improves the tensile properties of the sheath.

[0015] As a further technical solution, the mass of the modified magnesium oxide whiskers is ≥ the mass of the modified calcium carbonate.

[0016] In the present invention, the mass of the modified magnesium oxide whisker is greater than or equal to the mass of the modified calcium carbonate, thereby further improving the tensile properties of the sheath.

[0017] As a further technical solution, the mass ratio of the modified magnesium oxide whisker to the modified calcium carbonate is 2-4:1.

[0018] In the present invention, the mass ratio of the modified magnesium oxide whisker to the modified calcium carbonate is 2-4:1, which further improves the tensile properties of the sheath.

[0019] As a further technical solution, the preparation method of the modified magnesium oxide whisker comprises the following steps: dissolving the modifier in a solvent, mixing the modifier with the magnesium oxide whisker evenly, and drying to obtain the modified magnesium oxide whisker; the preparation method of the modified calcium carbonate comprises the following steps: dissolving the modifier in a solvent, mixing the modifier with the calcium carbonate evenly, and drying to obtain the modified calcium carbonate.

[0020] The present invention also proposes a production process for a high-strength unbonded prestressed steel bar, comprising the following steps: S1. Apply lubricating oil to the surface of the prestressed steel rod to obtain a pretreated prestressed steel rod; S2. After polyethylene, ethylene-vinyl acetate, filler, lubricant, antioxidant and light stabilizer are uniformly mixed, melt-extruded and coated on the surface of the pretreated prestressed steel rod, embossed and cooled to obtain a high-strength non-bonded prestressed steel rod.

[0021] The invention also proposes the application of the high-strength unbonded prestressed steel rod or the high-strength unbonded prestressed steel rod obtained by the production process in prestressed components in concrete structures.

[0022] The working principle and beneficial effects of the present invention are: The present invention provides a high-strength unbonded prestressed steel rod, comprising a prestressed steel rod, lubricating oil and a sheath, wherein the raw materials of the sheath include polyethylene, ethylene-vinyl acetate, fillers, lubricants, antioxidants and light stabilizers, and magnesium oxide whiskers and calcium carbonate are compounded as fillers to improve the tensile properties of the sheath and extend the service life of the unbonded prestressed steel rod. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The parameters of the raw materials in the following examples and comparative examples are as follows: Polyethylene is HDPE DMDA-8008H; Ethylene vinyl acetate is EVA4310; The MgO content in the magnesium oxide whisker is ≥99%, the diameter is 0.1~1.0μm, and the length is 5~100μm; The calcium carbonate is 1250 mesh light calcium carbonate.

[0025] Example 1 S1. Apply lubricating oil to the surface of the prestressed steel rod to obtain a pretreated prestressed steel rod; S2. 100 parts of polyethylene, 30 parts of ethylene-vinyl acetate, 1.5 parts of magnesium oxide whisker, 13.5 parts of calcium carbonate, 0.8 parts of lubricant AC-540A, 1 part of antioxidant 1010, 0.5 parts of antioxidant 626, and 0.3 parts of light stabilizer UV-144 are stirred at 120°C and 1000rpm for 30 minutes to mix evenly, and then transferred to a twin-screw extruder, extruded and coated on the surface of the pretreated prestressed steel rod at 200°C, embossed, and cooled to obtain a high-strength non-bonded prestressed steel rod with a sheath thickness of 1 mm.

[0026] Example 2 S1. Apply lubricating oil to the surface of the prestressed steel rod to obtain a pretreated prestressed steel rod; S2. 100 parts of polyethylene, 30 parts of ethylene-vinyl acetate, 1 part of magnesium oxide whisker, 9 parts of calcium carbonate, 0.5 parts of lubricant AC-540A, 0.5 parts of antioxidant 1010, and 0.1 parts of light stabilizer UV-531 are stirred at 120°C and 1000rpm for 30 minutes and mixed evenly, then transferred to a twin-screw extruder and extruded and coated on the surface of the pretreated prestressed steel rod at 200°C, embossed, and cooled to obtain a high-strength non-bonded prestressed steel rod with a sheath thickness of 1 mm.

[0027] Example 3 S1. Apply lubricating oil to the surface of the prestressed steel rod to obtain a pretreated prestressed steel rod; S2. 100 parts of polyethylene, 30 parts of ethylene-vinyl acetate, 2 parts of magnesium oxide whiskers, 18 parts of calcium carbonate, 1 part of lubricant AC-540A, 2 parts of antioxidant 168, and 0.5 parts of light stabilizer UV-531 are stirred at 120°C and 1000 rpm for 30 minutes to mix evenly, and then transferred to a twin-screw extruder, extruded and coated on the surface of the pretreated prestressed steel rod at 200°C, embossed, and cooled to obtain a high-strength non-bonded prestressed steel rod with a sheath thickness of 1 mm.

[0028] Example 4 S0, after dissolving 0.6 g of 2,5-dihydroxybenzoic acid in 200 g of ethanol, adding 20 g of magnesium oxide whisker and stirring at 500 rpm for 30 min to mix evenly, filtering and drying to obtain modified magnesium oxide whisker; after dissolving 1 g of 2,5-dihydroxybenzoic acid in 200 g of ethanol, adding 20 g of calcium carbonate and stirring at 500 rpm for 30 min to mix evenly, filtering and drying to obtain modified calcium carbonate; S1. Apply lubricating oil to the surface of the prestressed steel rod to obtain a pretreated prestressed steel rod; S2. 100 parts of polyethylene, 30 parts of ethylene-vinyl acetate, 1.5 parts of modified magnesium oxide whisker, 13.5 parts of modified calcium carbonate, 0.8 parts of lubricant AC-540A, 1 part of antioxidant 1010, 0.5 parts of antioxidant 626, and 0.3 parts of light stabilizer UV-144 are stirred at 120°C and 1000 rpm for 30 minutes to mix evenly, and then transferred to a twin-screw extruder, extruded and coated on the surface of the pretreated prestressed steel rod at 200°C, embossed, and cooled to obtain a high-strength non-bonded prestressed steel rod with a sheath thickness of 1 mm.

[0029] Example 5 The only difference from Example 4 is that: S0. After dissolving 0.6 g of lauric acid in 200 g of ethanol, add 20 g of magnesium oxide whisker and stir at 500 rpm for 30 min to mix evenly, filter and dry to obtain modified magnesium oxide whisker; after dissolving 1 g of lauric acid in 200 g of ethanol, add 20 g of calcium carbonate and stir at 500 rpm for 30 min to mix evenly, filter and dry to obtain modified calcium carbonate.

[0030] Example 6 The only difference from Example 4 is that: S0. After dissolving 0.6 g of 2,5-dihydroxybenzoic acid in 200 g of ethanol, add 20 g of magnesium oxide whisker and stir at 500 rpm for 30 min to mix evenly, filter and dry to obtain modified magnesium oxide whisker; after dissolving 1 g of lauric acid in 200 g of ethanol, add 20 g of calcium carbonate and stir at 500 rpm for 30 min to mix evenly, filter and dry to obtain modified calcium carbonate.

[0031] Example 7 The only difference from Example 4 is that: S0. After dissolving 0.6 g of lauric acid in 200 g of ethanol, add 20 g of magnesium oxide whisker, stir at 500 rpm for 30 min to mix evenly, filter, and dry to obtain modified magnesium oxide whisker; after dissolving 1 g of 2,5-dihydroxybenzoic acid in 200 g of ethanol, add 20 g of calcium carbonate, stir at 500 rpm for 30 min to mix evenly, filter, and dry to obtain modified calcium carbonate.

[0032] Example 8 The only difference from Example 7 is that: S2. 100 parts of polyethylene, 30 parts of ethylene-vinyl acetate, 7.5 parts of modified magnesium oxide whiskers, 7.5 parts of modified calcium carbonate, 0.8 parts of lubricant AC-540A, 1 part of antioxidant 1010, 0.5 parts of antioxidant 626, and 0.3 parts of light stabilizer UV-144 are stirred at 120°C and 1000 rpm for 30 minutes to mix evenly, and then transferred to a twin-screw extruder, extruded and coated on the surface of the pretreated prestressed steel rod at 200°C, embossed, and cooled to obtain a high-strength non-bonded prestressed steel rod with a sheath thickness of 1 mm.

[0033] Example 9 The only difference from Example 7 is that: S2. 100 parts of polyethylene, 30 parts of ethylene-vinyl acetate, 10 parts of modified magnesium oxide whiskers, 5 parts of modified calcium carbonate, 0.8 parts of lubricant AC-540A, 1 part of antioxidant 1010, 0.5 parts of antioxidant 626, and 0.3 parts of light stabilizer UV-144 are stirred at 120°C and 1000rpm for 30 minutes to mix evenly, and then transferred to a twin-screw extruder, extruded and coated on the surface of the pretreated prestressed steel rod at 200°C, embossed, and cooled to obtain a high-strength non-bonded prestressed steel rod with a sheath thickness of 1 mm.

[0034] Example 10 The only difference from Example 7 is that: S2. 100 parts of polyethylene, 30 parts of ethylene-vinyl acetate, 12 parts of modified magnesium oxide whiskers, 3 parts of modified calcium carbonate, 0.8 parts of lubricant AC-540A, 1 part of antioxidant 1010, 0.5 parts of antioxidant 626, and 0.3 parts of light stabilizer UV-144 are stirred at 120°C and 1000rpm for 30 minutes to mix evenly, and then transferred to a twin-screw extruder, extruded and coated on the surface of the pretreated prestressed steel rod at 200°C, embossed, and cooled to obtain a high-strength non-bonded prestressed steel rod with a sheath thickness of 1 mm.

[0035] Embodiment 11 The only difference from Example 7 is that: S2. 100 parts of polyethylene, 30 parts of ethylene-vinyl acetate, 13.5 parts of modified magnesium oxide whiskers, 1.5 parts of modified calcium carbonate, 0.8 parts of lubricant AC-540A, 1 part of antioxidant 1010, 0.5 parts of antioxidant 626, and 0.3 parts of light stabilizer UV-144 are stirred at 120°C and 1000rpm for 30 minutes to mix evenly, and then transferred to a twin-screw extruder, extruded and coated on the surface of the pretreated prestressed steel rod at 200°C, embossed, and cooled to obtain a high-strength non-bonded prestressed steel rod with a sheath thickness of 1 mm.

[0036] Comparative Example 1 The only difference from Example 1 is: S2. 100 parts of polyethylene, 30 parts of ethylene vinyl acetate, 15 parts of magnesium oxide whisker, 0.8 parts of lubricant AC-540A, 1 part of antioxidant 1010, 0.5 parts of antioxidant 626, and 0.3 parts of light stabilizer UV-144 are stirred at 120°C and 1000 rpm for 30 minutes to mix evenly, and then transferred to a twin-screw extruder, extruded and coated on the surface of the pretreated prestressed steel rod at 200°C, embossed, and cooled to obtain a high-strength non-bonded prestressed steel rod with a sheath thickness of 1 mm.

[0037] Comparative Example 2 The only difference from Example 1 is: S2. 100 parts of polyethylene, 30 parts of ethylene vinyl acetate, 15 parts of calcium carbonate, 0.8 parts of lubricant AC-540A, 1 part of antioxidant 1010, 0.5 parts of antioxidant 626, and 0.3 parts of light stabilizer UV-144 are stirred at 120°C and 1000 rpm for 30 minutes to mix evenly, and then transferred to a twin-screw extruder, extruded and coated on the surface of the pretreated prestressed steel rod at 200°C, embossed, and cooled to obtain a high-strength non-bonded prestressed steel rod with a sheath thickness of 1 mm.

[0038] According to the sheath formulas and processing methods of Examples 1 to 11 and Comparative Examples 1 to 2, samples with a thickness of 4 mm were processed and cut into type IA samples in GB / T 1040.2-2022. The tensile strength and elongation at break were tested with reference to the method in GB / T 1040.1-2018. The test speed was 50 mm / min, and the test results are recorded in Table 1.

[0039] Table 1 Tensile properties of sheath

[0040] It can be seen from Table 1 that the sheath tensile strength of the unbonded prestressed steel rod provided by the present invention is above 30.8 MPa and the elongation at break is above 400%, and it has high strength and good toughness, thereby providing a high-strength unbonded prestressed steel rod.

[0041] Compared with Comparative Examples 1-2, the tensile strength and elongation at break of the sheath obtained by using magnesium oxide whiskers and calcium carbonate in combination in Example 1 are higher than those in Comparative Examples 1-2, indicating that the compound use of magnesium oxide whiskers and calcium carbonate synergistically improves the tensile properties of the sheath.

[0042] The tensile strength and elongation at break of the sheaths obtained in Examples 4 to 7 are higher than those in Example 1, indicating that the magnesium oxide whiskers and calcium carbonate are further improved in tensile properties of the sheath after being modified with 2,5-dihydroxybenzoic acid or fatty acid.

[0043] The tensile strength and elongation at break of the sheath obtained in Example 7 are higher than those in Examples 4 to 6, indicating that the magnesium oxide whiskers are modified by fatty acids and the calcium carbonate is modified by 2,5-dihydroxybenzoic acid, which further improves the tensile properties of the sheath.

[0044] The tensile strength and elongation at break of the sheaths obtained in Examples 8 to 11 are higher than those in Example 7, indicating that the mass of the modified magnesium oxide whiskers is greater than or equal to the mass of the modified calcium carbonate, further improving the tensile properties of the sheath.

[0045] The tensile strength and elongation at break of the sheath obtained in Examples 9 to 10 are higher than those in Examples 8 and 11, indicating that the mass ratio of the modified magnesium oxide whisker to the modified calcium carbonate is 2 to 4:1, which further improves the tensile properties of the sheath.

[0046] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength unbonded prestressed steel rod, comprising a prestressed steel rod, lubricating oil and a sheath, characterized in that: The raw materials of the sheath include the following components in parts by mass: 100 parts of polyethylene, 30 parts of ethylene-vinyl acetate, 10-20 parts of filler, 0.5-1 part of lubricant, 0.5-2 parts of antioxidant, and 0.1-0.5 parts of light stabilizer. The filler includes magnesium oxide whisker and calcium carbonate in a mass ratio of 1:9-9:

1.

2. A high-strength unbonded prestressed steel bar according to claim 1, characterized in that: The magnesium oxide whisker is a modified magnesium oxide whisker, the calcium carbonate is a modified calcium carbonate, and the modifiers in the modified magnesium oxide whisker and the modified calcium carbonate are each independently 2,5-dihydroxybenzoic acid or fatty acid.

3. A high-strength unbonded prestressed steel bar according to claim 2, characterized in that: The modifier in the modified magnesium oxide whisker is fatty acid, and the modifier in the modified calcium carbonate is 2,5-dihydroxybenzoic acid.

4. A high-strength unbonded prestressed steel bar according to claim 3, characterized in that: The mass of the modified magnesium oxide whisker is greater than or equal to the mass of the modified calcium carbonate.

5. A high-strength unbonded prestressed steel bar according to claim 4, characterized in that: The mass ratio of the modified magnesium oxide whisker to the modified calcium carbonate is 2-4:

1.

6. A high-strength unbonded prestressed steel bar according to claim 2, characterized in that: The raw materials of the modified magnesium oxide whisker include a modifier and magnesium oxide whisker in a mass ratio of 0.3-1.2:

20.

7. A high-strength unbonded prestressed steel bar according to claim 2, characterized in that: The raw materials of the modified calcium carbonate include a modifier and calcium carbonate in a mass ratio of 0.5 to 1.5:

20.

8. The high-strength unbonded prestressed steel bar according to claim 2, characterized in that: The preparation method of the modified magnesium oxide whisker comprises the following steps: dissolving the modifier in a solvent, mixing the modifier with the magnesium oxide whisker uniformly, and drying to obtain the modified magnesium oxide whisker; the preparation method of the modified calcium carbonate comprises the following steps: dissolving the modifier in a solvent, mixing the modifier with the calcium carbonate uniformly, and drying to obtain the modified calcium carbonate.

9. A production process for high-strength unbonded prestressed steel bars according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Apply lubricating oil to the surface of the prestressed steel rod to obtain a pretreated prestressed steel rod; S2. After polyethylene, ethylene-vinyl acetate, filler, lubricant, antioxidant and light stabilizer are uniformly mixed, melt-extruded and coated on the surface of the pretreated prestressed steel rod, embossed and cooled to obtain a high-strength non-bonded prestressed steel rod.

10. Use of the high-strength unbonded prestressed steel rod according to any one of claims 1 to 8 or the high-strength unbonded prestressed steel rod obtained by the production process according to claim 9 in prestressed components in concrete structures.